Dynamic spectrum leasing and service selection in spectrum secondary market of cognitive radio networks - Zhu, Kun (2013)
We consider a problem of dynamic spectrum leasing in a spectrum secondary market of cognitive radio networks where secondary service providers lease spectrum from spectrum brokers to provide service to secondary users. The problem is challenging when the optimal decisions of both secondary providers and secondary users are made dynamically under competition. To address this problem, a two-level dynamic game framework is developed in this paper. Since the secondary users can adapt the service selection strategies according to the received service quality and price, the dynamic service selection is modeled as an evolutionary game at the lower level. The replicator dynamics is applied to model the service selection adaptation and the evolutionary equilibrium is considered to be the solution. With dynamic service selection, competitive secondary providers can dynamically lease spectrum to provide service to secondary users. A spectrum leasing differential game is formulated to model this competition at the upper level. Both simultaneous play model and asynchronous play model are considered. The service selection distribution of the underlying evolutionary game describes the state of the upper differential game. Both open-loop and closed-loop Nash equilibria are obtained as the solution of dynamic control of the differential game. Numerical comparison shows the advantages over static control in terms of profit and convergence speed.